2021
DOI: 10.1016/j.chemosphere.2021.129653
|View full text |Cite|
|
Sign up to set email alerts
|

Novel micro-structured carbon-based adsorbents for notorious arsenic removal from wastewater

Abstract: The contamination of groundwater by arsenic (As) in Bangladesh is the biggest impairing of a population, with a large number of peoples affected. Specifically, groundwater of Gangetic Delta is alarmingly contaminated with arsenic. Similar, perilous circumstances exist in many other countries and consequently, there is a dire need to develop cost-effective decentralized filtration unit utilizing low-cost adsorbents for eliminating arsenic from water.Morphological synthesis of carbon with unique spherical, nanor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 161 publications
2
7
0
Order By: Relevance
“…Carbon-based acid catalysts have several distinct advantages, including lower cost, due to the fact that they may be made from low-value biomass waste and have a large surface area and porosity [213]. This was in agreement with Table 3 findings, whereby the majority of the biomass-based catalysts exhibited high surface area (~13.30 to 1411 m 2 /g) and large pore size [167,168,172,[213][214][215]. Indeed, most of these studies still used the method of chemical activation method using H 2 SO 4 , H 3 PO 4 , and KOH for improving the acidity and textural properties of the activated carbon catalyst, hence promoting the catalytic esterification and transesterification reaction (FAME yield: 44-97%).…”
Section: Recent Trend Of Biomass-based Catalystsupporting
confidence: 86%
See 1 more Smart Citation
“…Carbon-based acid catalysts have several distinct advantages, including lower cost, due to the fact that they may be made from low-value biomass waste and have a large surface area and porosity [213]. This was in agreement with Table 3 findings, whereby the majority of the biomass-based catalysts exhibited high surface area (~13.30 to 1411 m 2 /g) and large pore size [167,168,172,[213][214][215]. Indeed, most of these studies still used the method of chemical activation method using H 2 SO 4 , H 3 PO 4 , and KOH for improving the acidity and textural properties of the activated carbon catalyst, hence promoting the catalytic esterification and transesterification reaction (FAME yield: 44-97%).…”
Section: Recent Trend Of Biomass-based Catalystsupporting
confidence: 86%
“…Albuquerque et al (2008) reported similar results of conversion using KOH/Na-X, CaO/SBA-15 catalysts, with 85% conversion at the reaction temperature of 60 • C and 95% conversion at reaction temperature of 65 • C, respectively. However, similar to the CaO discussed earlier, a reduction in activity was observed over time due to leaching of the active species and/or blockage of the active site arising from adsorption of organic molecules [171,172].…”
Section: Heterogeneous Base Catalysts For Biodiesel Productionsupporting
confidence: 63%
“…The removal of arsenic(V) from waters, wastewaters, or generally speaking, aqueous solutions, is a topic of the utmost importance for the scientific community though there are few technologies proposed for this task (Alka et al, 2021;Weerasundara and Bundschuh, 2021). Some recent investigations describe the use of micro-structured carbon-based (Islam et al, 2021) and modified incinerated sewage sludge ash (Gao et al, 2021) adsorbents; ion exchange using various resins (Dadakhanov et al, 2021), resin-supported nano-hydrated zirconium oxide (Deng et al, 2021), and an electrochemical-ion exchange hybrid method (Rathi et al, 2021); various membrane processes (Moreira et al, 2021;Sherugar et al, 2021;Rojas-Challa et al, 2021;Jarma et al, 2021;Lopez et al, 2021); and solvent extraction using a Triton X nonionic surfactant-choline chloride ionic liquid-water mixture (Silva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of tailored adsorbents for the effective removal of water pollutants is a challenge of particular interest especially for geogenic elements highly toxic like arsenic (Zhang et al, 2007;Davidescu et al, 2011;Ciopec et al, 2013;Negrea et al, 2014;Islam et al, 2021;Lv et al, 2021). This metalloid is cataloged as a priority groundwater pollutant and is hazardous for human beings even at very low concentrations (Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%